Association of height with inflammation and periodontitis: the Study of Health in Pomerania - Peter Meisel (Blackwell Synergy, 2007)
Aim: Short stature in adulthood has been associated with increased risk of health problems. Predisposition to inflammatory diseases might be associated with impaired length growth and impose a lifelong inflammatory burden. We tested this hypothesis in a cross-sectional population-based study with respect to periodontitis. Material and Methods: In 4290 randomly selected subjects from the normal population , we determined anthropometric measures and diagnostic periodontal parameters. Behavioural and environmental risk factors were assessed by interviews and questionnaires. Results: In regression analyses adjusted for age, gender, smoking, diabetes, education, and dental appointments, an inverse association was observed between height and clinical attachment loss. The magnitude of the association was higher in presence of risk factors smoking or diabetes. Odds ratios for smoking were 3.5 (2.2– 5.7%, 95% confidence interval) and 2.6 (1.5–4.3%) with the shortest and tallest height quartile, respectively. Figures for diabetes were 1.37 (1.04–1.80%) and 0.97 (0.67– 1.39%), respectively. Stratification for age and gender revealed that taller subjects had less periodontitis and decreased concentrations of markers of systemic inflammation than their shorter counterparts. Conclusion: This study is the first to associate height with periodontitis concluding that individuals born with a high susceptibility to infectious and inflammatory diseases may suffer from such diseases in childhood whereby the length growth could be impaired. Reaching adulthood, growth comes to a halt but the individual remains susceptible to inflammatory sequelae. Thus, smaller persons pertain a tendency to more severe periodontitis.